A QR (Quick Response) code application model in environmental management and education activities in a Neotropical botanical garden - Álvarez Loaiza, Pedro (2019)
We describe the generation of QR codes (Quick Response) for plant species and physical sections of the Reinaldo Espinosa Botanical Garden (Loja), the oldest in Ecuador, made with the purpose of providing visitors with a tool that allows them to have a better knowledge on specimens and promote greater interest in biodiversity conservation. The elements included for each species within the code were: floristic characteristics, origin and conservation status, as well as their ethnobotanical uses and image. The application of this new technology in a semi-natural area seeks to generate a more interactive guidance process, with more information. The proposal constitutes a management reference for the botanical gardens of the region